Study of alloferon, a novel immunomodulatory antimicrobial peptide (AMP), and its analogues - Appiah, Clara; Chen, Shitian; Pori, Afia Ibnat; Retyunskiy, Vladimir; Tzeng, Chimeng; Zhao, Ye (Frontiers in Pharmacology, 2024)
Antimicrobial peptides (AMPs) are widely distributed throughout the biosphere and represent a class of conserved peptide molecules with intrinsic antimicrobial properties.Their broad-spectrum antimicrobial activity and low risk to induce resistance have led to increased interest in AMPs as potential alternatives to traditional antibiotics. Among the AMPs, alloferon has been addressed due to its immunomodulatory properties that augment both innate and adaptive immune responses against various pathogens.Alloferon and its analogues have demonstrated pharmaceutical potential through their ability to enhance Natural Killer (NK) cell cytotoxicity and stimulate interferon (IFN) synthesis in both mouse and human models. Additionally, they have shown promise in augmenting antiviral and antitumor activities in mice. In this article, we provide a comprehensive review of the biological effects of alloferon and its analogues, incorporating our own research findings as well. These insights may contribute to a deeper understanding of the therapeutic potential of these novel AMPs.